Relationship between body composition and competition performance in swimming - Shephard, M. E.; Pritchard-Peschek, K. R.; Skinner T. L.; Bolam, K. A. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
In swimming, a multitude of physical, physiological, biomechanical and psychological parameters influence performance. While body composition is believed to be an important contributor to performance in swimming, with some coaches placing a strong emphasis on it during the training preparation phase, previous research is limited and inconclusive (Stager 1984; Siders et al. 1993; Carter & Ackland 1994; Anderson et al. 2008). Anthropometrical data of swimmers competing in the 1991 World Championships reported the best swimmers in all strokes were taller and had longer limb lengths (Carter & Ackland 1994). In that study the best performers in most strokes also had lower proportional skinfold thicknesses (Carter & Ackland 1994). In comparison to elite athletic groups in other sports such as running however, swimmers appear to have higher levels of body fat (Thorland et al. 1983). A study of adolescent female swimmers reported that while the faster swimmers had greater fat-free mass, there was no difference in body fat measurements compared with the slower swimmers (Stager et al. 1984). lt has been previously suggested that a certain level of body fat may be useful for swimmers, enhancing buoyancy and body position in the water, or by providing rounded body surfaces which are more favourable for streamlining with less drag characteristics (Stager et al. 1984; Bixler 2005).